COMMUNICATION MODELS OF THE BUSINESSES IN RELATION TO E-GOVERNMENT - Šimonová, Stanislava (Univerzita Pardubice, 2018)
Electronization and digitalization of the public administration services performance is one of the long-lasting priorities of the Czech Republic, of course in coordination with the European Union procedure, in correspondence with the strategies of the European committee oriented to the information and communication technologies (ICT) in the public administration. The eGovernment heads towards creating user friendly on-line services for businesses as well as citizens for decreasing administration work, for remote contact with the public administration. It also enables safe and protected services of the public administration. These visions are gradually realized by the ICT projects in coordination with connected legislation. It means, in its consequence, constantly changing environment which is difficult not only for the institutions of organs of public administration, but mainly difficult and burdensome for businesses out of the public administration. This text is focused on the situation of small and medium-sized businesses. These do not have specialized ICT departments, but must manage their performance of legal obligations towards the state, which means constantly changing and developing technological-legislative aspects of the eGovernment. This text maps the present basic communication models in relation to businesses towards the eGovernment.
KOMUNIKAČNÍ MODELY FIREM VE VZTAHU K E-GOVERNMENTU
Keywords: eGovernment conception; Public administration services; Communication models; Business company